Serum levels of apoptosis - related markers (P53, BCL-2, SFAS-L, CASPASE-9) in copd patients - Saduakassova, A.B.; Akparova, A.Yu.; Abdrahmanova, В. M.; Bersimbay, R.I. (National Laboratory Astana, Nazarbayev University 2016, 2016)
Apoptosis is a complex process of regulated and programmed cell death. In this process, the activation of many genes and signaling pathways is involved. Apoptosis provides a protective function due to the elimination of autoreactive immune cells and thus limits the destruction of their own cells and tissues. Of great interest is the study of the influence of apoptosis on a variety of pathological processes.
Keywords: apoptosis; COPD; Bcl-2; caspase-9; p-53; sFAS-L